A renovação das estratégias de lutas na agricultura: o caso das festas das sementes crioulas no sul do Brasil - Grígolo, Serinei César (2016)
The objective of this thesis was to examine the experiences with creole seeds as a resistance movement and to verify the cultural and symbolic significates associated with those seeds, mobilized for the transformation of society. We reconstructed through Bourdieu's notion of field, the field of seeds. This field is composed of professional agents linked to the seed industry as dominant agents, as well as agents of resistance, linked to social movements and organizations as dominated agents. Around the domination process, we structure the practices by which dominant agents reproduces himself and resistance strategies used by dominated agents. The reconstitution of the field of seeds was made with analysis of bibliographies produced by the field agents and it reveals that the dominant pole of the field of seeds, in its general characteristics, emerges from hybrid seeds and it is consolidated with the transgenia. From its genesis to its consolidation receives significant contributions of the science and politics fields. On the other hand, the resistance agents depend on diversified struggle strategies, with emphasis on creole seeds feasts. We take for to study the Creole Seeds feasts of the South of Brazil and some practices of resistance of Mexico. We take the feasts as symbolic instruments and constituent of counter-hegemonic movements. The primary data were obtained mainly through observation, informal interviews, sounds and photographic records of the places visited like a museums, universities, research institutions, feasts and fairs. The study points out that the resistance occurs in the broad context, that is, to agriculture model as a specific way, and in defense of creole seeds. The production creole seeds as a symbolic good, denies the market, constitute producer groups that are recognize and legitimize, are born and reinforced from autonomous productions, but, above all, in the face of the dominant logic, has been requiring of the participants the construction of the other possible, in what is understood as struggles for to transform the society. This study contributes with analysis of the reach of symbolic production both for to maintenance as to subvert the domination on the industrial seeds.